The efficacy and safety of probiotics for prevention of chemoradiotherapy-induced diarrhea in people with abdominal and pelvic cancer: A systematic review and meta-analysis based on 23 randomized studies. (December 2020) - Lin, Shuang; Shen, Yufei
Abstract: Background and aims: We evaluated the efficacy and safety of probiotics for prevention of chemoradiotherapy-induced diarrhea in patients with abdominal or pelvic cancer. Methods: We searched the Cochrane Library, PubMed, EMBASE, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Wanfang, and VIP databases up to August 2019. We also hand searched the citation lists of included studies and previous systematic reviews identified to identify further relevant trials. The primary outcome was the incidence of chemoradiotherapy-induced diarrhea of all grades. The secondary outcomes were improvement of antidiarrheal medication use, stool form (Bristol scale), response rate, and adverse events (AEs). Diarrhea was graded according to the Common Toxicity Criteria system. Two reviewers assessed trial quality and extracted data independently. The included studies were analyzed using Review Manager ver. 5.2. Results: Twenty-three randomized, placebo-controlled studies (N = 2570 participants) were included in the efficacy assessment. The incidence of all diarrhea (risk ratio [RR] 0.16; 95% confidence interval [CI] 0.51–0.73), grade ≥ 3 diarrhea (RR 0.36; 95% CI 0.18–0.72), and grade ≥ 2 diarrhea (RR 0.65; 95% CI 0.54–0.78), but not that of grade ≤ 2 diarrhea (RR 1.07; 95% CI 0.95–1.21), was significantly reduced in the probiotics compared to the placebo groups. No significant increase in the incidence of AEs was found in the probiotics group, although four studies reported a variety of AEs. Conclusions: Probiotics prevented chemoradiotherapy-induced diarrhea, particularly high-grade diarrhea. Probiotics rarely cause AEs. Highlights: Probiotics reduced the incidence of CRID, particularly the CTC grade ≥ 2 or ≥ 3 diarrhea. However, probiotics did not reduce the frequency of CTC grade ≤2 CRID. Probiotics rarely cause any adverse events.